Cardiovascular and Renal Outcomes of Incretin-based Therapies: A Review of Recent Clinical Trials - Kyriakos, Georgios; Quiles-Sanchez, Lourdes V.; Garmpi, Anna; Farmaki, Paraskevi; Kyre, Konstantina; Gkogkos, Spyridon; Savvanis, Spyridon; Memi, Eleni (Current Cardiology Reviews, 2020)
Background: To report the cardiovascular and renal effects of incretin-based therapies. Methods: The studies of clinical trials on incretin-based therapy published in medical journals from the years 2010 to 2017 were comprehensively searched using MEDLINE and EMBASE with no language restriction. The studies were reviewed and the cardiovascular and renal risks reported were recorded. Results: Incretin-based therapeutics represent novel and promising anti-diabetes drugs, the direct cardiovascular actions which may translate into demonstrable clinical benefits on cardiovascular outcomes. Furthermore, incretin-based therapies do not adversely affect renal function.
Keywords: clinical trials